The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1073/pnas.2221688120
|View full text |Cite
|
Sign up to set email alerts
|

The spontaneous symmetry breaking in Ta 2 NiSe 5 is structural in nature

Abstract: The excitonic insulator is an electronically driven phase of matter that emerges upon the spontaneous formation and Bose condensation of excitons. Detecting this exotic order in candidate materials is a subject of paramount importance, as the size of the excitonic gap in the band structure establishes the potential of this collective state for superfluid energy transport. However, the identification of this phase in real solids is hindered by the coexistence of a structural order parameter with the same symmet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 48 publications
(85 reference statements)
0
5
0
Order By: Relevance
“… 22 account for the phase transition from the Cmcm phase to the C 2/ c phase as driven by the BEC of excitonic electron–hole pairs, while a more recent report suggests that spontaneous symmetry breaking is mostly structural in nature. 23 This symmetry-lowering distortion accompanying the formation of the excitonic insulator phase allows mixing of the conduction and valence bands at Γ, and this mixing is proposed 24 to account for the observation of flattening of the bands around Γ in ARPES experiments and the interpretation of the ARPES data using an electronic description, which suggests a Ta(IV) d 1 state and an oxidized Ni 3d 9 /Se-ligand-hole state. 22 , 24 , 25 Further experiments devoted to fully understanding the transition are the topic of current research.…”
Section: Introductionmentioning
confidence: 99%
“… 22 account for the phase transition from the Cmcm phase to the C 2/ c phase as driven by the BEC of excitonic electron–hole pairs, while a more recent report suggests that spontaneous symmetry breaking is mostly structural in nature. 23 This symmetry-lowering distortion accompanying the formation of the excitonic insulator phase allows mixing of the conduction and valence bands at Γ, and this mixing is proposed 24 to account for the observation of flattening of the bands around Γ in ARPES experiments and the interpretation of the ARPES data using an electronic description, which suggests a Ta(IV) d 1 state and an oxidized Ni 3d 9 /Se-ligand-hole state. 22 , 24 , 25 Further experiments devoted to fully understanding the transition are the topic of current research.…”
Section: Introductionmentioning
confidence: 99%
“…10 To date, the studies on Ta 2 NiSe 5 mainly focus on photo-induced enhancement of EIs, 14,15 photo-induced phase transition, 16,17 collective amplitude modes, 18,19 the optical manipulations of EI order parameters 20,21 and the origin of the phase transition (structural or electronic). [22][23][24] Larkin et al demonstrated giant exciton Fano resonance in Ta 2 NiSe 5 and attributed this observation to large oscillator strength of spatially extended exciton-phonon bound states. 25 Edoardo et al performed time resolved ARPES (trARPES) to track the electronic and crystal structure of Ta 2 NiSe 5 and pointed out that the spontaneous symmetry breaking is structurally driven.…”
Section: Introductionmentioning
confidence: 99%
“…25 Edoardo et al performed time resolved ARPES (trARPES) to track the electronic and crystal structure of Ta 2 NiSe 5 and pointed out that the spontaneous symmetry breaking is structurally driven. 22 Katsumi et al attributed electron correlations to the nature of the EI transition. 23 In terms of the coherent modes, Bretscher et al observed an anomalous propagation velocity of B10 5 m s À1 and attributed it to the hybridization between phonon modes and the phase mode of the condensate.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most fascinating physical properties of Ta 2 NiSe 5 is the dramatic photoinduced effect similar to TiSe 2 , [ 17 ] which has been discussed in various contexts. [ 18–24 ]…”
Section: Introductionmentioning
confidence: 99%